The compensation funds and regional developtment and its impact on comunities benefiting from the generalized system of royalties (2013)
The following essay is the result of a literature review on the Compensation Funds and Regional Development and its impact on communities benefiting from the Generalized System of Royalties. Within a year of its implementation, different public and private entities have questioned the effectiveness in achieving the purpose for which the General System of Royalties was created. It’s also of highly importance for the beneficiary communities of the system, since it’s a source of resources for investment projects that meet basic needs of the public